Immunoinformatics Study on Early 4 Protein of Human Papillomavirus Type 16 for Cervical Cancer Vaccine Peptide Candidate - Yani Suryani; Opik Taupiqurrohman; Muhammad Yusuf; Toto Subroto; Sukma Nuswantara (UIN Sunan Gunung Djati Bandung, 2019)
Â The aims of this study were to carry out testing of the early 4 protein of type 16 HPV through immunoinformatics meth-ods in an effort to get the peptide vaccine candidate for cervical cancer. The software used are IEDB-AR, CABSdock and Accelrys Discovery Study 4.5. Based on the analysis that sequence of ami-no acid lysine, leucine, leucine, glycine, serine, threonine, tryp-tophan, proline and threonine (KLLGSTWPT) and the sequence of amino acid tyrosine, tyrosine, valine, leucine, histidine, leucine, cysteine, leucine, alanine, alanine, threonine, lysine, tyrosine, pro-line and leucine (YYVLHLCLAATKYPL) are peptide vaccine can-didate for cervical cancer from the early 4 protein of HPV type 16Â